Synthesis of Novel Fluorinated Benzofurans and Dihydrobenzofurans - Hariss, Layal; Bouhadir, Kamal H.; Roisnel, Thierry; Grée, René; Hachem, Ali (Synlett, 2017)
Starting from easily accessible propargylic fluorides an intramolecular oxa-Michael addition affords, in good yields, new gem-difluorodihydrobenzofurans bearing an electrophilic double bond in position 2. On these intermediates nucleophilic additions and Diels–Alder reactions have been performed affording functionalized fluorinated dihydrobenzofurans. On the other hand, Pd-catalyzed defluorinations give the corresponding fluorine containing benzofurans.
Keywords: fluorine; gem-difluoropropargyls; benzofurans; 2,3-dihydrobenzofurans; oxa-Michael additions; heterocycles